Cell-free, quantitative mineralization measurements as a proxy to identify osteoinductive bone graft substitutes. (August 2021) - Maazouz, Yassine; Chizzola, Giacomo; Döbelin, Nicola; Bohner, Marc
Abstract: Some synthetic bone graft substitutes (BGS) can trigger ectopic bone formation, which is the hallmark of osteoinduction and the most important prerequisite for the repair of large bone defects. Unfortunately, measuring or predicting BGS osteoinductive potential based on in vitro experiments is currently impossible. A recent study claimed that synthetic BGS can induce bone formation ectopically if they create a local homeostatic imbalance during their in vivo mineralization. This raised the hope that a simple cell free in vitro mineralization experiment would correlate with osteoinduction. The aim of the present study was therefore to assess the ability of a quantitative in vitro mineralization test to predict and rank the osteoinductive potential of BGS. Eight calcium phosphate BGS already tested ectopically in 9 different in vivo studies were used for that purpose. The experiment was able to identify materials that are reliably osteoinductive from those that are not, but was inaccurate in ranking the osteoinductive materials between each other. Chemical contaminants (Ca 2+, Mg 2+, H +, OH −, PO4 3− ) present in some of the BGS affected the in vitro mineralization experiment results, but not in a direction that could explain the different rankings. In conclusion, this study suggests that an in vitro experiment can be used as a fast and reliable screening tool to identify osteoinductive BGS and underline the need to study ionic contaminants on calcium phosphate BGS. Graphical abstract: Image 1